Generation Z’s awareness towards halal restaurants in Selangor - Misri, Syamim Mahirah (2018)
Nowadays, in Malaysia, the number of restaurants that serve Japanese, Korean, Indonesian, Thailand, Italian and Western cuisine has increase where more than 85% of Malaysian frequently visiting those restaurants. However, most of the restaurants are not certified by Halal yet due to firstly, the application was rejected by JAKIM, secondly, the application is in the process and lastly the business itself has no intention to apply for the certificate. However, these businesses operate their business by displaying “pork free” sign while some restaurants have manually written HALAL word to gain Muslims trust. But, halal is not just “pork free” but the ingredients used such as emulsifiers (gelatin, enzymes, lecithin, glycerin), stabilizer, coloring, and flavoring may cause doubtful. Generation Z is easily attracted to new things, thus there is high possibility that they will visit those restaurants. There are three objectives for this study which are first, to investigate the awareness level of generation Z towards halal restaurants, second, to examine association between socio demographic and the level of awareness on Halal restaurants and lastly to determine factors that influence Generation Z towards Halal restaurants. The total of 350 respondents is collected by using cluster sampling at Petaling District, Selangor. The data obtained from respondents was analyzed by using descriptive analysis, chi square tests and factor analysis. Results show from total average mean shows that the awareness level among generation Z towards halal restaurants is low. Chi-square test was test was applied to examine the association between socio-demographic variables and generation Z awareness towards halal restaurants in Selangor. Result shows that different gender, race, number of household, education level and residential area had association towards the awareness level among generation Z. Factor analysis was conducted determine the factors that affecting the awareness of generation Z in choosing halal restaurants by reducing five to eight statements or items that had been asked. Result shows that they were five factors that will influence awareness towards halal restaurant. The factors are responsibilities towards religion, health reasons, halal certification and logo, attitude and lifestyle factor. As a conclusion, since the awareness level among generation Z is decreasing, food marketers have to increase their knowledge why halal is important to life so that their awareness towards halal food will increase. JAKIM also play an important role as JAKIM is the only body that could certify halal food certifications, so they have to do extension program such as awareness advertisement through social media.